Performa dan lama berahi sapi Peranakan Simmental yang memperoleh penambahan kecambah kacang hijau dalam pakan - Annisa Ayu Febrianti; Enny Tantini Setiatin; Daud Samsudewa (Livestock and Animal Research, 2022)
Objective: The aims of this research were to observe the effect of mung bean sprouts to the estrous performance (onset, vulva condition, cervical mucus, behavior, pH of cervical mucus and spinnbarkeit) and length of the estrous on Simmental grade cow.Methods: The materials used in this study were 12 Simmental grade cow with characteristics aged 3 – 4 years, average of weights 399.51 ± 29.97kg, BCS 3 – 4, had normal estrous cycle and had parturition minimum one. The cow were divided into 4 groups; control without mung bean sprouts addition (T0), 250g mung bean sprouts (T1), 375g mung bean sprouts (T2) and 500g mung bean sprouts (T3). The cow was given mung bean sprout during 7 days before estrous. Data of onset, vulva condition, cervical mucus, behaviour, pH of cervical mucus and spinnbarkeit) and length of the estrous analyzed with non-parametric Kruskal-Wallis H test significancy 5% using software Statistical Package for the Social Sciences (SPSS) versi 20.Results: The result showed that estrous performance (onset estrous, vulva condition, cervical mucus, behaviour, pH of cervical mucus, spinnbarkeit) and length of the estrous with mung bean sprout addition were non significantly different on Simmental grade cow.Conclusions: According to non-parametric Kruskal-Wallis H test adding mung bean sprouts given the same effect with control.